Trusting Cloud Computing for Personal Files - Mazlina, Abdul Majid; Jaber, Aws Naser; Mohamad Fadli, Zolkipli; Shahid, Anwar (IEEE, 2014)
In a recent research study concerning current and future (state-of-the-art) cloud security issues, we recognized a substantive number of security loopholes in information technology systems, and devised relevant solutions for such problems. As an outcome, exchanging the main point that contains all the information originating from heterogeneous sources that oversee the physiological methodologies of a city could have devastating effects because cloud security would be influenced at diverse levels and clients would be influenced at distinctive administrations. In addition, if these innovations are utilized more extensively, cyber terrorism could, with a solitary machine ambush, hinder significant urban areas worldwide. This paper summarizes some major issues in cloud computing, which caused us to reconsider the type of information that can be stored safely in cloud computing.